Analisis Kinerja Guru Di SMA Negeri 1 Tambusai Tahun Pembelajaran 2015/2016 - Harahap, Rasidi (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This research purpose to know the performance of teachers in Senior Hight School 1 Tambusai. This research using descriptive research. The population of this research are all the teachers in hight school Negeri 1 Tambusai with totaly 31 people. Use saturated sample for take sampling, that means all members of the population sampled. Techniques of collecting data uses questionnaire with Likert scale technique. The result of analysis data showed mastery of the material with an average percentage of 91.00%, the embodies creativity with an average percentage of 91.00%, the utilization of teaching time with an average percentage of 92.00%, an understanding of students with an average percentage of 86. 00%, and mastery of the state of the class with an average percentage of 94.00%. The result of all indicator getting an average percentage of 91.00% with good criteria.